Developing a decision model for project management methodology selection - James, Motlalepula (Rhodes University, 2026)
Background: Implementation of successful information technology (IT) projects that meet user requirements has increased the visibility of project management (PM) approaches. With IT projects being robust and dynamic due to the evolving nature of user requirements, choosing the most suitable project management methodology presents a challenge. The challenge lies in the absence of an integrated framework that incorporates available methodologies and best practices to create a unified view of the most suitable approach for an IT project. Decision models are essential tools that enable organizations to assist project managers and practitioners in choosing the most appropriate methodology for implementing IT projects. When implemented correctly, decision models are powerful tools that lead to increased competitive advantage. Moreover, project managers and practitioners in South Africa face major challenges when it comes to choosing the appropriate project management methodology. The known issues are unclear project scope, communication breakdowns, inadequate risk management, and difficulties in managing stakeholder expectations. As such, assessing the development of an IT Project Management Decision Model is essential to assist project manager and practitioner when implementing projects. Objective: Using project management theory as an underpinning lens, the purpose of this study is to investigate the distinguishing characteristics, advantages, and disadvantages of an agile approach (such as Scrum) versus plan-driven /stage-gate methods based on a Traditional Waterfall process from the perspective of IT project managers and practitioners. This study focuses on generating a decision model that guides IT project managers in selecting the appropriate project management methodology for implementing IT projects in South Africa. Methods: A qualitative multi-method research approach was utilised in this study by making use of an interpretive paradigm, abductive reasoning, qualitative description research strategy, and semi-structured interviews as data collection methods to elicit feedback on the study’s IT Project Management Decision Model. Document analysis was conducted to rank the project management characteristics in order of relevance, and thematic analysis was conducted to categorise and code the interview data. Findings: It was found that the relevant IT decision model elements to consider are project management phases, project management methodology process, and project management methodology process recommendations. Four project management phases are identified: concept, development, implementation, and closeout. Each phase has Traditional and Agile processes that can be combined to create Hybrid processes that appropriately suit each IT project implementation.
evidence from the South African IT sector
Keywords: Project management (http://id.loc.gov/authorities/subjects/sh85065919); Information technology projects (http://id.loc.gov/authorities/subjects/sh2006004039); Scrum (Computer software development) (http://id.loc.gov/authorities/subjects/sh2001003039); Agile software development (http://id.loc.gov/authorities/subjects/sh2007006411); Agile project management (http://id.loc.gov/authorities/subjects/sh2018001560); Information Systems; Decision model (https://www.wikidata.org/wiki/Q5249242)